2014
DOI: 10.1159/000362885
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Ultrasonography with a Guide Sheath for Pure or Mixed Ground-Glass Opacity Lesions

Abstract: Background: Ground-glass opacity (GGO) lesions are difficult to diagnose by transbronchial biopsy (TBB). Objectives: We attempted to diagnose solitary peripheral GGO predominant-type lesions by TBB using endobronchial ultrasonography with a guide sheath (EBUS-GS) under X-ray fluoroscopic guidance, and to evaluate several factors associated with diagnostic yield. Methods: The medical records of 67 patients with GGO predominant-type lesions who underwent TBB using EBUS-GS under X-ray fluoroscopic guidance were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 28 publications
4
51
6
Order By: Relevance
“…Although peripheral GGO predominant-type lesions are difficult to diagnose by bronchoscopy, there have been several reports demonstrating a promising diagnostic yield by TBB using EBUS-GS [14,27]. This is the first study to demonstrate a promising diagnostic yield for peripheral GGO predominant-type lesions by TBB using EBUS-GS and VBN; of the 169 lesions included in the present study, 116 (69%) were successfully diagnosed by this method.…”
Section: Commentmentioning
confidence: 51%
See 3 more Smart Citations
“…Although peripheral GGO predominant-type lesions are difficult to diagnose by bronchoscopy, there have been several reports demonstrating a promising diagnostic yield by TBB using EBUS-GS [14,27]. This is the first study to demonstrate a promising diagnostic yield for peripheral GGO predominant-type lesions by TBB using EBUS-GS and VBN; of the 169 lesions included in the present study, 116 (69%) were successfully diagnosed by this method.…”
Section: Commentmentioning
confidence: 51%
“…We previously reported that EBUS-GS without VBN could be useful in clinical practice for diagnosing GGO predominant-type lesions in the peripheral lung, and described the advantages of EBUS-GS [14]. Especially, in the case of pure GGO, the change in brightness on EBUS images was very delicate when the EBUS probe was in and out of the lesions (Figure 1c).…”
Section: Commentmentioning
confidence: 93%
See 2 more Smart Citations
“…The following studies reported that the diagnostic yield of EBUS-GS for PPLs was between 57% and 90%, and it was proved to be a safe procedure with low rate of pneumothorax and hemoptysis (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Till now there is only one randomized controlled study (22) comparing the two procedures.…”
Section: Introductionmentioning
confidence: 99%